Determining media use competencies in media literacy curriculum design for the digital society: a modified 2-wave Delphi method - Mohamed Salleh, Sabariah; Shamshudeen, Rosya Izyanie; Wan Abas, Wan Anita; Tamam, Ezhar (Taylor's University Lakeside Campus, 2019)
Media literacy is vital for the proper functioning and well-being of individuals in a democratic society. However, an equally important consideration which has not been adequately addressed is ensuring that the media literacy course syllabus in schools and universities are relevant to the needs and challenges of the contemporary society. A modified two-wave Delphi study was carried out to gauge the opinions of stakeholders pertaining to the important aspects of media-related knowledge that young people in a digital society should be well-versed in. A total of 75 and 44 respondents participated in the 1st wave and 2nd wave respectively, representing different relevant stakeholders in the media industry and education sector. The study employed one-on-one and face-to-face interviews, using structured questionnaires. Findings of the study suggest that, from a Malaysian sociocultural perspective, media competence comprises not only understanding about media behaviour (media communication function, biasness, representation, influence, and credibility) but also encompasses moral and legal obligations in media use. In addition, understanding the normative dimension of responsible and accountable media culture is the path towards empowering and emancipating young people in using and experiencing the media for a positive self and societal development.